Social Factors Affecting Students' Social Isolation (Case Study: Islamic Azad University Central Tehran Branch) - zahra hazrati someeh; Malihe Dadashali (توسعه اجتماعی, 2018)
The study examines the factors affecting Islamic Azad University Central Tehran Branch students' social isolation is studied. From this perspective, the integrated approach based on the theory of Durkheim, Simmel, Ztvmka, Johnson, Chalabi, Kravt, Wellman and Dreyfus used and with respect to assumptions that of the theory according to the characteristics of the study population received attempts to identify the impact of trust and the use of cyberspace and background variables on the emergence of social isolation. With A survey uses questionnaires to 370 students of Islamic Azad University Central Tehran Branch (Integrated University of Valiasr) that through simple random sampling and quota sample size was calculated using the formula were selected. In this study, content and formal validity and Cronbach's alpha was used to measure reliability. Research data using the regression, T-test and ANOVA were analyzed. The results obtained direct and positive impact between trust and social isolation shows (53/3), this means that distrust is increasing social isolation. Also the use of cyberspace (0/017) and background variables (employment status, marital status, place of residence, educational level) as the independent variables research is not affected. on social isolation whatsoever. However, the amount of age group is significantly different to the breakdown of social isolation. Regression results indicate that 29.4% of the variation in the independent variables cause changes in social isolation. The results of this study show that distrust is preventing cooperation among students and weakening the social bonds.